Surface modification method of inorganic fiber
Through the reaction of pre-softening and surface treatment liquid under mechanical conditions, the problem of organic matter removal on the surface of inorganic fibers is solved, efficient modification and performance improvement of the surface of inorganic fibers is achieved, and the use of toxic solvents is avoided.
Patent Information
- Application Number
- CN202411213534.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art is difficult to quickly and efficiently remove organic matter from the surface of inorganic fibers, and commonly used methods can lead to reduced fiber strength and use toxic and harmful solvents.
The organic matter on the surface of the inorganic fibers is treated with pre-softening, and then placed in the prepared surface treatment liquid for reaction under mechanical conditions. The surface treatment liquid includes penetrant, cosolvent, functional additive, pH adjuster and water. Through water molecules spreading and mechanical action, organic matter on the surface of the fiber is removed and modified.
On the basis of not damaging the properties of inorganic fibers, quickly and effectively remove organic matter on the fiber surface, improve the surface state of the fiber, improve the performance of composite materials, and avoid the use of toxic solvents.
Smart Images

Figure CN119411397A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a surface modification method for inorganic fibers. Background Art
[0002] Generally, coating an organic composition on the surface of inorganic fibers can improve the textile properties of the fibers and prevent them from suffering from greater mechanical damage during the manufacturing or textile process. At the same time, in order to ensure the softness of the inorganic fibers and meet the requirements of related subsequent textile processing, the coated organic composition generally has the characteristics of low molecular weight, low degree of cross-linking and some components being hydrophilic.
[0003] With the continuous expansion of the application fields of composite materials, the application fields and application environments of fiber-reinforced composite materials have become more complicated, resulting in the inability of conventional sizing agent coating to meet the needs of special fields. Therefore, it is necessary to modify the inorganic fibers according to the application fields and application environments of composite materials to meet the needs of subsequent process applications. For some special fields, it is often necessary to modify and modify the surface of inorganic fibers through some special means to enhance the performance of the fiber matrix on the material.
[0004] For example, Chinese patent CN110258120A discloses a method for producing electronic-grade glass fiber cloth, which is pre-cleaned with deionized water, then smoldered at 350-400°C to remove organic matter on the surface of the glass fiber, and then coated with the configured organic matter to prepare a glass fiber modified product. However, since the glass fiber needs to be smoldered at high temperature, the cracks in the glass fiber expand and cause the strength of the glass fiber to decay, which cannot meet the requirements of high strength. Chinese patent CN109608672A proposes a method for coating glass fiber with nano-silicon dioxide particle treatment agent to improve the high temperature resistance of composite products, which uses distilled water above 90°C and boils for more than 20 to remove organic matter on the fiber surface, and then applies the configured nano-silicon dioxide particle treatment agent to the fiber surface. However, this method takes too long to process, and it is difficult to remove the water-soluble organic matter on the fiber surface. Chinese patent CN1022495578 proposes a method for modifying the surface of glass fiber, which is to ablate at 300-500℃ for 30 minutes, and then immerse the ablated sample in a solvent such as toluene, acetone, THF or mixed acid, and then immerse for 4-12 hours to fully remove the surface organic matter, and then coat the glass surface with nano-silicon dioxide particles in a sol. However, this method uses ablation and toxic and harmful treatment agents to treat the fiber, and then performs modification and coating, which is complicated and takes a long time to process.
[0005] In summary, it can be seen that the method of modifying the inorganic fiber after removing the organic matter on the surface of the inorganic fiber in the related art is not only difficult to quickly remove the organic matter on the surface of the inorganic fiber, but the treatment process is likely to cause the strength of the inorganic fiber to decrease. At the same time, the surface treatment agent used is usually a toxic and harmful solvent, which is not conducive to production and preparation.
[0006] Therefore, based on the above problems, there is an urgent need to provide a surface modification method for inorganic fibers. Summary of the invention
[0007] The embodiment of the present invention provides a surface modification method for inorganic fibers, which can quickly and effectively remove organic matter on the surface of the inorganic fibers and modify the inorganic fibers without damaging the performance of the inorganic fibers.
[0008] In a first aspect, the present invention provides a method for surface modification of an inorganic fiber, the method comprising:
[0009] (1) Pre-softening of organic matter on the surface of inorganic fibers;
[0010] (2) Under mechanical conditions, the pre-softened inorganic fiber is placed in a prepared surface treatment liquid for reaction to modify the surface of the inorganic fiber; the surface treatment liquid includes a penetrant, a co-solvent, other functional additives, a pH adjuster and water.
[0011] Preferably, in step (1), the pre-softening temperature is 120-140° C. and the time is 1-3 h;
[0012] Preferably, in step (2), the mechanical conditions include mechanical stirring or ultrasonic treatment, and the reaction temperature is 50-100° C. and the reaction time is 10-720 min.
[0013] Preferably, the penetrant is at least one of fatty alcohol polyoxyethylene ethers, alkanolamides or alkyl quaternary ammonium salts;
[0014] The cosolvent is at least one of monoalcohols, polyols or amides;
[0015] The other functional additives are at least one of alkoxylated amines, amine oxide salts, and silane coupling agents;
[0016] The pH adjuster is at least one of a monocarboxylic acid, a dicarboxylic acid or a tribasic organic acid.
[0017] Preferably, in terms of mass percentage, the addition amounts of the raw materials in the surface treatment liquid are: 0.2-2% of penetrant, 0.5-5% of cosolvent, 0.1-2% of other functional additives, 0.2-2% of pH regulator and water.
[0018] Preferably, the surface treatment liquid further comprises magnetic nano-microspheres and / or modified nano-particles having a core-shell structure.
[0019] Preferably, the mass ratio of the added amount of the core-shell structured nanoparticles in the surface treatment liquid does not exceed 5%, and the mass ratio of the added amount of the modified nanoparticles in the surface treatment liquid does not exceed 5%.
[0020] Preferably, the shell of the core-shell magnetic nanoparticles is silicon dioxide, modified silicon dioxide, epoxy resin or methyl methacrylate, and the core is ferric oxide, ferroferric oxide or nickel-based alloy;
[0021] The modified nanoparticles are modified nano silicon dioxide or modified nano aluminum oxide.
[0022] Preferably, the particle size of the shell of the magnetic nanosphere is 50-500 nm, and the particle size of the core is 50-100 nm; the particle size of the modified nanoparticle is 10-50 nm.
[0023] Preferably, the step of placing the pre-softened inorganic fiber in a prepared surface treatment liquid for treatment comprises:
[0024] (21) adding the penetrant, cosolvent, other functional additives and pH adjuster into water and stirring to obtain a mixed mother solution;
[0025] (22) placing the pre-softened inorganic fiber in the mixed mother solution for reaction under mechanical conditions to obtain a reaction mixture;
[0026] (23) Adding magnetic nanospheres with a core-shell structure and modified nanoparticles to the reaction mixture in batches, and removing organic matter on the surface of the inorganic fiber by using a magnetic field after the reaction to modify the surface of the inorganic fiber.
[0027] Preferably, after step (23), the method further includes the steps of washing and drying the surface-modified inorganic fibers in sequence.
[0028] In a second aspect, the present invention provides an inorganic fiber obtained by modification using any modification method described in the first aspect.
[0029] Compared with the prior art, the present invention has at least the following beneficial effects:
[0030] In the present invention, the inorganic fiber is first pre-softened to destroy the organic system bonded to the fiber surface, and then the pre-softened inorganic fiber is placed in a prepared surface treatment liquid. At this time, the various additives in the surface treatment liquid can promote the spreading of water molecules on the fiber surface, causing the fiber surface coating layer to swell, thereby invading the interior, causing some substances free from the resin system to detach and destroy and modify the membrane structure, while mechanical action is used to accelerate the destruction of the organic membrane structure on the fiber surface and the stripping of uncross-linked substances, so that the inorganic fiber surface can be modified in a targeted manner; it can be seen that the present scheme can remove organic matter on the fiber surface without high temperature in an aqueous environment, and while efficiently modifying the fiber surface coating structure, it has no significant effect on the performance of the fiber matrix itself, and on this basis, the fiber surface can also be modified. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 It is a flow chart of a surface modification method of an inorganic fiber provided by the present invention;
[0033] Figure 2 It is a schematic diagram of the microstructure of a surface-modified inorganic fiber provided by the present invention after being treated by treatment processes in different embodiments. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0035] As mentioned above, for inorganic fiber surface modification, the required modifier is generally applied to the inorganic fiber surface at the fiber bundle stage or the textile oil coated on the inorganic fiber surface is first thoroughly removed by cleaning, and then the fiber used as the reinforcing material is surface modified by applying the relevant modifier. At the same time, the current methods for removing organic matter on the surface of inorganic fibers are mostly solvent cleaning (such as acetone, toluene, etc.), and these polar solvents are very harmful. Another method is conventional thermal decomposition, which removes organic matter on the surface of inorganic fibers by oxidative decomposition of organic matter under high temperature conditions, but this method often causes a significant loss in the mechanical properties of the inorganic fibers after removal.
[0036] Therefore, based on the above issues, Figure 1 As shown, the present invention provides a method for surface modification of inorganic fibers, the method comprising:
[0037] (1) Pre-softening of organic matter on the surface of inorganic fibers;
[0038] (2) Under mechanical conditions, the pre-softened inorganic fiber is placed in a prepared surface treatment liquid for reaction to modify the surface of the inorganic fiber; the surface treatment liquid includes a penetrant, a co-solvent, other functional additives, a pH adjuster and water.
[0039] In an embodiment of the present invention, the inorganic fiber is first pre-softened to destroy the organic system bonded to the fiber surface, and then the pre-softened inorganic fiber is placed in a prepared surface treatment liquid. At this time, the various additives in the surface treatment liquid can promote the spreading of water molecules on the organic matter bonded to the fiber surface, and at the same time, assisted by mechanical action, which is beneficial to accelerate the destruction of the organic film structure on the fiber surface, and effectively remove the substances that are not completely cross-linked on the surface, so as to better modify the surface of the inorganic fiber; it can be seen that the present scheme can remove organic matter on the fiber surface without high temperature in an aqueous environment, and while efficiently removing the organic components on the fiber surface, it has no significant impact on the performance of the fiber matrix itself, and at the same time, the modification of the fiber surface can be achieved on this basis.
[0040] According to some preferred embodiments, in step (1), the pre-softening temperature is 120-140°C (for example, 120°C, 125°C, 130°C, 135°C or 140°C), and the time is 1-3h (for example, 1h, 2h or 3h).
[0041] In an embodiment of the present invention, the inorganic fiber is first pre-softened and then placed in a surface treatment liquid. By reasonably controlling the pre-softening temperature, it will not damage the performance of the inorganic fiber itself, and at the same time it will help accelerate the swelling rate of organic matter coated on the surface of the inorganic fiber in the surface treatment liquid, thereby improving the removal efficiency of organic matter on the surface of the inorganic fiber.
[0042] According to some preferred embodiments, in step (2), the mechanical conditions include mechanical stirring or ultrasonic treatment, the reaction temperature is 50-100°C (for example, it can be 50°C, 60°C, 70°C, 80°C, 90°C or 100°C), and the time is 10-720min (for example, it can be 10min, 30min, 60min, 120min, 180min, 240min, 300min, 360min, 480min, 600min or 720min).
[0043] In an embodiment of the present invention, in order to enable the surface treatment liquid to better react with the organic matter on the surface of the pre-softened inorganic fiber, the prepared surface treatment liquid is first heated to the above-mentioned reaction temperature, and then the pre-softened inorganic fiber is quickly placed in the surface treatment liquid. At this time, the penetrant, cosolvent and other functional additives in the surface treatment liquid can promote the spreading of water molecules on the surface of the organic component coated on the fiber surface, and at the same time, mechanical conditions such as mechanical stirring and ultrasound are used to remove the organic matter that is not completely cross-linked on the surface of the inorganic fiber, and accelerate the destruction of the organic membrane structure by other components in the surface treatment liquid under the action of mechanical conditions, and promote the cosolvent and other components to accelerate the invasion into the interior of the organic composition, so as to promote its full swelling and separation from the surface of the inorganic fiber.
[0044] It should be noted that the present invention has no particular limitation on the rotation speed of mechanical stirring and the frequency of ultrasonic treatment, and those skilled in the art can make reasonable selections according to actual needs without causing damage to the inorganic fibers.
[0045] According to some preferred embodiments, the penetrant is at least one of fatty alcohol polyoxyethylene ethers, alkanolamides or alkyl quaternary ammonium salts; the cosolvent is at least one of monoalcohols, polyols or amides; the other functional additives are at least one of alkoxylated amines, amine oxides, polyoxyethylene ethers or silane coupling agents; the pH adjuster is at least one of monocarboxylic acids, dicarboxylic acids or phosphoric acid.
[0046] In the embodiment of the present invention, when preparing the surface treatment liquid, the penetrant, cosolvent and other functional additives are first added to water at 25-50°C and mixed, and then the pH value of the mixed liquid is adjusted to 5.5-6.5 using a pH adjuster to obtain a surface treatment liquid. During use, the penetrant in the surface treatment liquid can fix the hydrophilic and lipophilic groups in the organic matter on the fiber surface and promote the spreading of water molecules on the organic surface; the presence of the cosolvent can promote the swelling of the organic matter on the inorganic fiber surface, and other functional additives such as alkoxylated amines, amine oxides, and silane coupling agents can cross-link with the swollen organic matter on the fiber surface, thereby further promoting the rapid separation of the bonded organic matter from the inorganic fiber surface. The pH adjuster is used to keep the pH value of the surface treatment liquid between 5.5-6.5, which is conducive to further modification of the inorganic fiber surface.
[0047] It should be noted that in the embodiment of the present invention, when the penetrant is a fatty alcohol polyoxyethylene ether, it can specifically be the penetrant JFC, when the penetrant is an alkanolamide, it can specifically be N,N-bis(hydroxyethyl)dodecylamide, and when the penetrant is an alkane quaternary ammonium salt, it can specifically be hexadecyl ammonium bromide; when the co-solvent is a monoalcohol, it can specifically be n-butanol, the co-solvent can be a polyol with a carbon chain number of 1-6, such as ethylene glycol, propylene glycol or glycerol, and when the co-solvent is an amide, it can specifically be diethylamide; other additives can be selectively added according to the properties of the organic matter coated on the surface of the specifically treated inorganic fiber and the final treatment effect of the inorganic fiber, such as dodecyl dimethyl amine oxide, KH-550 or KH-570.
[0048] According to some preferred embodiments, the amount of each raw material added to the surface treatment liquid is, by mass percentage, 0.2-2% of penetrant (for example, 0.2%, 0.5%, 1%, 1.5% or 2%), 0.5-5% of cosolvent (for example, 0.5%, 1%, 2%, 3%, 4% or 5%), 0.1-2% of other functional additives (for example, 0.1%, 0.5%, 1%, 1.5% or 2%), 0.2-2% of pH adjuster (for example, 0.2%, 0.5%, 1%, 1.5% or 2%) and 89-99% of water (for example, 89%, 90%, 92%, 95%, 97% or 99%).
[0049] The experiment of the present invention confirms that by controlling the content of each component in the surface treatment liquid within the above-mentioned range, it is possible to efficiently remove the organic components on the surface of the inorganic fiber without damaging the performance of the inorganic fiber itself, and on this basis, the surface of the inorganic fiber can be further modified to a better level; in the embodiment of the present invention, if the amount of penetrant added is too low, the penetration of the surface treatment liquid will be reduced, which is not conducive to promoting the spreading of water molecules on the surface of the organic matter, and if the amount of penetrant added is too high, the surface energy of the organic matter will increase, which is not conducive to the sufficient contact between the solubilizer and other functional additives and the organic matter on the surface of the inorganic fiber; if the amount of solubilizer added is too low, it is not conducive to promoting the sufficient swelling of the organic components on the surface of the inorganic fiber, and adding too much solubilizer will make the penetrant and other functional additives free outside the organic reaction system, which is not conducive to the effective removal of the organic components on the surface of the inorganic fiber.
[0050] According to some preferred embodiments, the surface treatment liquid further includes magnetic nano-microspheres and / or modified nano-particles with a core-shell structure; the mass ratio of the added amount of the core-shell structured nano-particles in the surface treatment liquid does not exceed 5%, and the mass ratio of the added amount of the modified nano-particles in the surface treatment liquid does not exceed 5%.
[0051] In the embodiment of the present invention, the surface treatment liquid may further include magnetic nano-microspheres and / or modified nano-particles having a core-shell structure. When the surface treatment liquid contains magnetic nano-microspheres having a core-shell structure, the magnetic nano-microspheres can combine with the organic composition swollen in the aqueous solution and some organic components that are not completely cross-linked with the surface of the inorganic fiber through physical adsorption, chemical adsorption, and steric effect, thereby effectively removing organic matter on the surface of the inorganic fiber and organic components free in the system, providing a guarantee for subsequent surface modification. When the surface treatment liquid contains modified nano-particles, after the pre-softened inorganic fiber is placed in the surface treatment liquid, Under mechanical action, the organic components that are not completely cross-linked on the surface of the inorganic fiber can be removed, and the organic components can be fully swelled on the surface of the inorganic fiber. At this time, the modified nanoparticles can combine with the surface of the inorganic fiber to modify it, thereby improving the surface state of the fiber and improving the performance of the fiber and composite materials; when the surface treatment liquid contains core-shell structured magnetic nanoparticles and modified nanoparticles, the magnetic nanoparticles can effectively remove organic matter on the surface of the inorganic fiber and organic components free in the system, thereby effectively preventing organic molecules from being free in the system and combining with the inorganic fiber again, hindering the modification of the inorganic fiber surface by the modified nanoparticles.
[0052] According to some preferred embodiments, the shell of the core-shell magnetic nanospheres is silicon dioxide, epoxy resin or methyl methacrylate, and the core is ferric oxide, ferroferric oxide or nickel-based alloy; the modified nanoparticles are modified nano silicon dioxide or modified nano alumina.
[0053] According to some preferred embodiments, the particle size of the shell of the core-shell structured magnetic nanoparticles is 50-500nm (for example, it can be 50nm, 100nm, 200nm, 300nm, 400nm or 500nm), and the particle size of the core is 50-100nm (for example, it can be 50nm, 60nm, 70nm, 80nm, 90nm or 100nm); the particle size of the modified nanoparticles is 10-50nm.
[0054] In an embodiment of the present invention, by adopting the above-mentioned type of core-shell structured magnetic nano-microspheres, it is possible to effectively remove the organic composition on the surface of inorganic fibers without damaging the performance of the organic fibers. At the same time, by controlling the particle size of the core-shell structured magnetic nano-microspheres and the particle size of the modified nano-particles within the above-mentioned range, it is possible to ensure a larger specific surface area of the nano-microspheres, so that the modified nano-particles can fully react with the surface of the inorganic fibers, thereby ensuring a better modification effect on the surface of the inorganic fibers, and at the same time being beneficial to the subsequent cleaning of the organic fibers.
[0055] According to some preferred embodiments, the pre-softened inorganic fiber is placed in a prepared surface treatment liquid for treatment, comprising:
[0056] (21) adding the penetrant, cosolvent, other functional additives and pH adjuster into water and stirring to obtain a mixed mother solution;
[0057] (22) placing the pre-softened inorganic fiber in the mixed mother solution for reaction under mechanical conditions to obtain a reaction mixture;
[0058] (23) Adding magnetic nanospheres with a core-shell structure and modified nanoparticles to the reaction mixture in batches, and removing organic matter on the surface of the inorganic fiber by using a magnetic field after the reaction to modify the surface of the inorganic fiber.
[0059] In an embodiment of the present invention, when the surface treatment liquid contains magnetic nano-microspheres and / or modified nano-particles with a core-shell structure, in order to achieve surface modification of the inorganic fiber in one step and improve the modification effect, it is necessary to add the magnetic nano-microspheres and modified nano-particles with a core-shell structure to the reaction mixture in batches. This helps to avoid the influence of other components in the surface treatment liquid on the magnetic nano-microspheres and modified nano-particles. Then, magnetic separation is performed using a magnetic field, which is beneficial to better modify the fiber surface and to remove impurities in the surface treatment liquid without replacing the treatment liquid in batches.
[0060] For example, in this embodiment, inorganic fibers coated with resin on the surface are used as the treatment object, and the surface treatment liquid includes a penetrant, a cosolvent, other functional additives, a pH regulator, magnetic nano-microspheres with a core-shell structure, modified nanoparticles and water. Specifically, the penetrant, the cosolvent, other functional additives and the pH regulator are first added to water and stirred to obtain a mixed mother liquor, and the temperature of the mixed mother liquor is heated to 50-100°C, and then the pre-softened inorganic fibers are quickly placed in the mixed mother liquor, and reacted under mechanical conditions for 10-720 minutes. At this time, the penetrant, the cosolvent and other functional additives promote the spreading of water molecules on the resin surface, remove the partially incompletely cross-linked substances on the surface under mechanical action, and accelerate the destruction of the resin coating structure, so as to fully swell the resin on the surface of the inorganic fibers, thereby making it free in the aqueous solution.
[0061] Afterwards, magnetic nano-microspheres and modified nano-particles are added to the reaction mixture in batches. At this time, the organic components free in the aqueous solution can be captured and adsorbed by the magnetic nano-particles for multiple times, and the magnetic nano-particles that adsorb the organic components will adsorb and grow the stripped resin molecules in constant movement, thereby effectively removing the resin molecules free in the system. The magnetic nano-particles are then removed by a magnetic field. Under the magnetic traction between the magnetic field and the magnetic nano-microspheres, the resin molecules gradually strip off the fully swollen resin, thereby stripping off the resin wrapped on the surface of the inorganic fibers. While the magnetic nano-microspheres capture and adsorb the resin components, the modified nano-particles can continuously contact and react with the surface of the inorganic fibers, thereby enhancing the performance of the inorganic fibers.
[0062] It can be seen that in the embodiment of the present invention, the magnetic nanoparticles are firstly coupled with the organic components on the surface of the inorganic fiber under the traction of the magnetic field through the paramagnetism of the magnetic nanoparticles, and the low molecular weight and low cross-linking degree organic components are stripped and cleared by the force, thereby completely removing the organic matter on the fiber surface, and effectively preventing the organic molecules from being free in the system and combining with the inorganic fiber again, eliminating the interference of free organic molecules attached to the fiber surface and the surface of the modified nanoparticles, allowing the inorganic fiber to fully combine with the modified nanoparticles, thereby improving the surface state of the inorganic fiber and improving the performance of the fiber and the composite material.
[0063] According to some preferred embodiments, after step (23), the step of washing and drying the surface-modified inorganic fibers in sequence is also included.
[0064] In an embodiment of the present invention, after the surface of the inorganic fiber is modified by the surface treatment liquid, the inorganic fiber can be cleaned 1-3 times with ethanol and water with a mass concentration of 75% respectively to remove the surface treatment liquid on the surface of the inorganic fiber, and finally placed in an oven at 80-160°C for 30-360 minutes.
[0065] The surface modification method of inorganic fibers in the embodiment of the present invention can effectively and thoroughly remove organic coatings on the surface of inorganic fibers without significantly affecting the performance of the inorganic fibers themselves. It can also remove non-polar molecules on the fiber surface that affect the composite of the substrate, etch the fiber interface, increase the surface roughness, and increase the composite performance of the fiber and other materials, thereby better realizing the surface modification of the inorganic fibers, and there is no need to completely remove the organic matter coating the surface of the inorganic fibers. At the same time, this method can also be used to remove components on the surface of the inorganic fibers that are not conducive to surface interface bonding, increase the roughness of the interface, and improve the application performance of the fiber in composite materials.
[0066] In order to more clearly illustrate the technical solution and advantages of the present invention, a surface modification method of an inorganic fiber is described in detail through several embodiments below;
[0067] In the embodiments of the present invention, the magnetic nanoparticles were purchased from Aladdin Reagent Co., Ltd., the magnetic nanoparticles with core-shell structure were synthesized by the Sturb method, and the modified nanoparticles were purchased from Aladdin Reagent Co., Ltd., and corresponding chemical modifications were performed according to the requirements.
[0068] Embodiment 1:
[0069] The inorganic fiber is an alkali-free glass fiber fabric coated with an epoxy resin impregnant on the surface, and the surface treatment liquid includes: a penetrant, a cosolvent, other functional additives, a pH regulator, magnetic nano-microspheres with a core-shell structure, modified nano-particles and water;
[0070] (1) Pre-soften the inorganic fiber in an oven at 130°C for 2 h;
[0071] (2) placing the pre-softened inorganic fiber in a prepared surface treatment solution for treatment;
[0072] (21) 4 g of a penetrant (2 g of hexadecyl ammonium bromide and 2 g of fatty alcohol polyoxyethylene ether AEO-8), 9 g of a cosolvent (4 g of triacetamide and 5 g of propylene glycol), 1 g of other functional additives (silane coupling agent KH550 and) and 5 g of a pH adjuster (glacial acetic acid) were added to 85 g of water and stirred to obtain a mixed mother liquor;
[0073] (22) Under mechanical conditions (ultrasonic conditions), the pre-softened inorganic fibers are placed in a mixed mother solution at a temperature of 95 °C for reaction for 100 min to obtain a reaction mixture;
[0074] (23) 1.5 g of core-shell magnetic nanoparticles (modified silica with a shell particle size of 100 nm and ferrosoferric oxide with a core particle size of 50 nm) and 0.1 g of modified nanoparticles (silane-modified nanosilica with a particle size of 50 nm) were divided into four equal parts and added to the reaction mixture in four batches. After each addition of the magnetic nanoparticles, the reaction was allowed to react for 35 min. A magnetic field was then connected to the reaction tank for 3 min, and the attached magnetic nanoparticles were removed through an isolation membrane to modify the surface of the inorganic fiber.
[0075] (3) The surface-modified inorganic fiber was washed three times with 75% ethanol and deionized water respectively, and then placed in an oven at 120° C. for 120 min to obtain the modified inorganic fiber.
[0076] Embodiment 2:
[0077] The inorganic fiber is a quartz fiber fabric with a surface coated with an enhanced impregnating agent, and the surface treatment liquid includes: a penetrant, a cosolvent, other functional additives, a pH regulator, magnetic nano-microspheres with a core-shell structure, modified nano-particles and water;
[0078] (1) Pre-soften the inorganic fiber in an oven at 120°C for 2 h;
[0079] (2) placing the pre-softened inorganic fiber in a prepared surface treatment solution for treatment;
[0080] (21) 2 g of a penetrant (JFC), 14 g of a cosolvent (4 g of triacetamide, 5 g of ethanol, and 5 g of isopropanol), 1 g of other functional additives (silane coupling agent KH550 and 2 g of octylphenol polyoxyethylene ether), and 5 g of a pH adjuster (glacial acetic acid) were added to 85 g of water and stirred to obtain a mixed mother liquor;
[0081] (22) Under mechanical conditions (mechanical stirring conditions), placing the pre-softened inorganic fiber in a mixed mother liquor at a temperature of 90° C. for reaction for 100 min to obtain a reaction mixture;
[0082] (23) 0.8 g of core-shell structured magnetic nanoparticles (modified silica with a shell size of 200 nm and ferroferric oxide with a core size of 100 nm) and 0.1 g of modified nanoparticles (silane-modified SiO2 nanoparticles with a particle size of 20 nm) were divided into three equal parts and added to the reaction mixture in three batches. After each addition of the magnetic nanoparticles, the reaction was allowed to react for 35 min, and then a magnetic field was connected to the reaction tank for 3 min. The attached magnetic nanoparticles were then removed through an isolation membrane to modify the surface of the inorganic fiber.
[0083] (3) The surface-modified inorganic fiber was washed twice with 75% ethanol and deionized water respectively, and then placed in an oven at 80° C. for 240 min to obtain a modified quartz fiber fabric.
[0084] Embodiment 3:
[0085] The inorganic fiber is an alumina fiber coated with an enhanced impregnating agent on the surface, and the surface treatment liquid includes: a penetrant, a cosolvent, other functional additives, a pH regulator, a core-shell structured magnetic nano-microsphere, modified nano-particles and water;
[0086] (1) Pre-soften the inorganic fiber in an oven at 140°C for 1 h;
[0087] (2) placing the pre-softened inorganic fiber in a prepared surface treatment solution for treatment;
[0088] (21) adding 2 g of a penetrant (JFC), 9 g of a cosolvent (4 g of triacetamide and 5 g of ethanol), 3 g of other functional additives (1 g of a silane coupling agent KH570 and 2 g of octylphenol polyoxyethylene ether), and 5 g of a pH adjuster (glacial acetic acid) to 81 g of water, stirring and mixing to obtain a mixed mother liquor;
[0089] (22) placing the pre-softened inorganic fiber in a mixed mother liquor at a temperature of 90° C. for reaction for 40 min under mechanical conditions (mechanical stirring) to obtain a reaction mixture;
[0090] (23) 1 g of core-shell magnetic nanoparticles (epoxy resin with a shell particle size of 300 nm and ferrosoferric oxide with a core particle size of 100 nm) and 0.1 g of modified nanoparticles (modified nanoalumina microspheres with a particle size of 30 nm) were divided into two equal parts and added to the reaction mixture in two batches. After each addition of the magnetic nanoparticles and the modified nanoparticles, the reaction was allowed to react for 35 min. A magnetic field was then connected to the reaction tank for 3 min, and the attached magnetic nanoparticles were removed through an isolation membrane to modify the surface of the inorganic fiber.
[0091] (3) The surface-modified inorganic fiber was washed once with 75% ethanol and once with deionized water, and then placed in an oven at 120° C. for 120 min to obtain the modified inorganic fiber.
[0092] Embodiment 4:
[0093] The inorganic fiber is an alkali-free glass fiber fabric coated with a reinforced impregnating agent on the surface, and the surface treatment liquid includes: a penetrant, a cosolvent, other functional additives, a pH regulator, magnetic nano-microspheres with a core-shell structure, modified nano-particles and water;
[0094] (1) Pre-soften the inorganic fiber in an oven at 120°C for 1 h;
[0095] (2) placing the pre-softened inorganic fiber in a prepared surface treatment solution for treatment;
[0096] (21) 2 g of a penetrant (JFC), 9 g of a cosolvent (4 g of triacetamide, 5 g of ethanol and 5 g of isopropanol), 3 g of other functional additives (1 g of a silane coupling agent KH550 and 2 g of octylphenol polyoxyethylene ether) and 5 g of a pH adjuster (glacial acetic acid) were added to 81 g of water and stirred to obtain a mixed mother liquor;
[0097] (22) Under mechanical conditions (ultrasonic conditions), the pre-softened inorganic fibers were placed in a mixed mother solution at a temperature of 95 °C for 30 min to modify the surface of the inorganic fibers;
[0098] (3) The surface-modified inorganic fiber was washed three times with 75% ethanol and deionized water respectively, and then placed in an oven at 120° C. for 120 min to obtain the modified inorganic fiber.
[0099] Embodiment 5:
[0100] The inorganic fiber is an alkali-free glass fiber coated with an epoxy resin-type impregnating agent on the surface, and the surface treatment liquid includes: a penetrant, a cosolvent, other functional additives, a pH regulator, magnetic nano-microspheres including a core-shell structure, and water;
[0101] (1) Pre-soften the inorganic fiber in an oven at 130°C for 1 h;
[0102] (2) placing the pre-softened inorganic fiber in a prepared surface treatment solution for treatment;
[0103] (21) adding 2 g of a penetrant (2 g of hexadecyl ammonium bromide), 9 g of a cosolvent (4 g of triethylamide and 5 g of propylene glycol), 3 g of other functional additives (silane coupling agent KH550 and 2 g of fatty alcohol polyoxyethylene ether AEO-8), and 5 g of a pH adjuster (glacial acetic acid) to 79 g of water, stirring and mixing to obtain a mixed mother liquor;
[0104] (22) placing the pre-softened inorganic fiber in a mixed mother liquor at a temperature of 95 °C for reaction for 30 min under mechanical conditions (ultrasonic conditions) to obtain a reaction mixture;
[0105] (23) 1 g of core-shell magnetic nanoparticles (silane-modified silica with a shell particle size of 500 nm and ferrosoferric oxide with a core particle size of 100 nm) was added to the reaction mixture. After the addition of the magnetic nanoparticles, the reaction was allowed to react for 10 min. A magnetic field was then connected to the reaction tank for 3 min, and the attached magnetic nanoparticles were removed through an isolation membrane to modify the surface of the inorganic fiber.
[0106] (3) The surface-modified inorganic fiber was washed once with 75% ethanol and once with deionized water, and then placed in an oven at 120° C. for 120 min to obtain the modified inorganic fiber.
[0107] Embodiment 6:
[0108] The inorganic fiber is a high-strength glass fiber coated with an epoxy resin impregnant on the surface, and the surface treatment liquid includes: a penetrant, a cosolvent, other functional additives, a pH regulator, magnetic nano-microspheres with a core-shell structure, and water;
[0109] (1) Pre-soften the inorganic fiber in an oven at 120°C for 1 h;
[0110] (2) placing the pre-softened inorganic fiber in a prepared surface treatment solution for treatment;
[0111] (21) adding 1 g of a penetrant (hexadecyl ammonium bromide), 4 g of a cosolvent (2 g of triethylamide and 2 g of propylene glycol), 2 g of other functional additives (1 g of a silane coupling agent KH550 and 1 g of a fatty alcohol polyoxyethylene ether AEO-8), and 3 g of a pH adjuster (glacial acetic acid) to 80 g of water, stirring and mixing to obtain a mixed mother liquor;
[0112] (22) Under mechanical conditions (ultrasonic conditions), the pre-softened inorganic fibers are placed in a mixed mother liquor at a temperature of 95 °C for reaction for 20 min to obtain a reaction mixture;
[0113] (23) 0.5 g of core-shell magnetic nanoparticles (silane-modified silica with a shell particle size of 100 nm and ferrosoferric oxide with a core particle size of 50 nm) were added to the reaction mixture. After the addition of the magnetic nanoparticles and the reaction was allowed to react for 10 min, a magnetic field was connected to the reaction tank and maintained for 3 min. The attached magnetic nanoparticles were then removed through an isolation membrane to modify the surface of the inorganic fiber.
[0114] (3) The surface-modified inorganic fiber was washed three times with 75% ethanol and deionized water respectively, and then placed in an oven at 120° C. for 120 min to obtain the modified inorganic fiber.
[0115] Embodiment 7:
[0116] Example 7 is basically the same as Example 1, except that the surface treatment liquid does not contain magnetic nanoparticles with a core-shell structure.
[0117] Embodiment 8:
[0118] Example 8 is basically the same as Example 1, except that the core-shell structured magnetic nano-microspheres in the surface treatment liquid are silicon dioxide with an outer shell particle size of 100 nm and ferrosoferric oxide with an inner core particle size of 50 nm.
[0119] Embodiment 9:
[0120] Example 9 is basically the same as Example 1, except that: in step (23), 2 g of magnetic nanospheres with a core-shell structure (silane-modified silica with an outer shell particle size of 100 nm and ferrosoferric oxide with an inner core particle size of 50 nm) and 1 g of modified nanoparticles (modified silica with a particle size of 50 nm) are directly added to the reaction mixture. After reacting for 140 minutes, a magnetic field is connected to the reaction tank and maintained for 3 minutes, and then the attached magnetic nanoparticles are removed through an isolation membrane to modify the surface of the inorganic fiber.
[0121] Embodiment 10:
[0122] Example 10 is substantially the same as Example 1, except that the surface treatment liquid does not contain magnetic nano-microspheres and modified nano-particles with a core-shell structure.
[0123] Embodiment 11:
[0124] Example 11 is basically the same as Example 1, except that the amount of penetrant added to the surface treatment liquid is 3 g.
[0125] Embodiment 12:
[0126] Example 12 is basically the same as Example 1, except that the amount of solvent added to the surface treatment liquid is 6 g.
[0127] Embodiment 13:
[0128] Example 13 is basically the same as Example 1, except that the amount of the core-shell structured magnetic nanoparticles added to the surface treatment liquid is 6 g.
[0129] Embodiment 14:
[0130] Example 14 is basically the same as Example 1, except that: in step (2), 4g of penetrant (2g of hexadecyl ammonium bromide and 2g of fatty alcohol polyoxyethylene ether AEO-8), 9g of co-solvent (4g of triacetamide and 5g of propylene glycol), 1g of other functional additives (silane coupling agent KH550 and), 5g of pH adjuster (glacial acetic acid), 2g of core-shell magnetic nano-microspheres (modified silica with an outer shell particle size of 100nm and ferrosoferric oxide with an inner core particle size of 50nm) and 1g of modified nanoparticles (silane-modified silica with a particle size of 50nm) are added to 78g of water and stirred to obtain a surface treatment solution; under mechanical conditions (ultrasonic conditions), the pre-softened inorganic fiber is placed in the surface treatment solution at a temperature of 95°C for reaction for 100min to obtain a reaction mixture to modify the surface of the inorganic fiber.
[0131] Comparative Example 1:
[0132] Comparative Example 1 is substantially the same as Example 1, except that it does not include step (1), that is, directly placing the inorganic fiber in the surface treatment liquid to react under mechanical conditions.
[0133] Comparative Example 2:
[0134] The inorganic fiber is a glass fiber cloth coated with a wetting agent on the surface. The surface treatment liquid is prepared as follows: half of the total water volume of deionized water is put into a preparation tank, and the pH value is adjusted to about 3.5 with acetic acid. At a stirring speed of 150 rpm, dodecyltrimethoxysilane is slowly added and stirred for 40 minutes. The solution is clear and there is no oil on the surface. The pH value is measured; the stirring speed is controlled at 150 rpm, and quaternary ammonium salt, isooctyl alcohol, bisphenol A epoxy resin, polyurethane emulsion, and the remaining deionized water are added to the prepared solution in sequence to adjust the pH value to about 5.5.
[0135] (1) coating the prepared sizing agent on the surface of glass fiber, performing pre-treatment, and weaving to obtain a product;
[0136] (2) The product is heat treated at a speed of 45 m / min and at 360° C. by continuous desizing in a KH furnace to burn off 80% of the slurry, and then simmered in a BH furnace at 380° C. for 50 h to reduce the residual slurry rate of the glass fiber cloth to 0.05%. The surface treatment liquid is then used to perform surface chemical treatment to obtain a finished glass fiber cloth.
[0137] The modified inorganic fibers in Examples 1 to 14 and Comparative Examples 1 to 2 were subjected to performance tests, and the test data are shown in Table 1.
[0138] Performance test method or standard:
[0139] Organic matter removal rate: in accordance with GB / T 9914.2-2013 Test methods for reinforced products Part 2: Determination of combustible content of glass fiber. Dry yarn tensile strength: in accordance with GB / T7690.3 Test methods for yarns of reinforced materials Part 3: Determination of breaking strength and breaking elongation of glass fiber. Composite material performance test: in accordance with the national standard GB / T1447-2005 fiber reinforced plastic tensile performance test method, the tensile properties and elastic modulus of composite materials are tested; in accordance with the national standard GB / T1450.1-2005 fiber reinforced plastic interlaminar shear strength test method, the interlaminar shear strength of composite material interlaminar plates is tested;
[0140] Table 1
[0141]
[0142] Note: “--” means the performance cannot be tested
[0143] From Table 1 and Figure 2 It can be seen that the modification method and surface treatment liquid in the embodiment of the present invention are used to modify the surface of inorganic fibers, which can not only effectively remove the organic components on the surface of inorganic fibers, but also will not damage the performance of the inorganic fibers themselves, and at the same time can better modify the surface of inorganic fibers to better enhance the performance of inorganic fibers.
[0144] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for surface modification of inorganic fibers, characterized in that: The method comprises: (1) Pre-softening of organic matter on the surface of inorganic fibers; (2) Under mechanical conditions, the pre-softened inorganic fiber is placed in a prepared surface treatment liquid for reaction to modify the surface of the inorganic fiber; the surface treatment liquid includes a penetrant, a co-solvent, other functional additives, a pH adjuster and water.
2. The method according to claim 1, characterized in that In step (1), the pre-softening temperature is 120-140° C. and the time is 1-3 h; and / or In step (2), the mechanical conditions include mechanical stirring or ultrasonic treatment, the reaction temperature is 50-100° C., and the reaction time is 10-720 min.
3. The method according to claim 1, characterized in that The penetrant is at least one of fatty alcohol polyoxyethylene ethers, alkanolamides or alkyl quaternary ammonium salts; The cosolvent is at least one of monoalcohols, polyols or amides; The other functional additives are at least one of alkoxylated amines, amine oxide salts or silane coupling agents; The pH adjuster is at least one of a monocarboxylic acid, a dicarboxylic acid or a tribasic organic acid.
4. The method according to claim 1, characterized in that: In terms of mass percentage, the added amounts of various raw materials in the surface treatment liquid are: 0.2-2% of penetrant, 0.5-5% of cosolvent, 0.1-2% of other functional additives, 0.2-2% of pH regulator and 89-99% of water.
5. The method according to claim 1, characterized in that: The surface treatment liquid also includes magnetic nano-microspheres and / or modified nano-particles of core-shell structure; Preferably, the mass ratio of the added amount of the core-shell structured nanoparticles in the surface treatment liquid does not exceed 5%, and the mass ratio of the added amount of the modified nanoparticles in the surface treatment liquid does not exceed 5%.
6. The method according to claim 5, characterized in that The shell of the core-shell magnetic nano-microspheres is silicon dioxide, modified silicon dioxide, epoxy resin or methyl methacrylate, and the core is ferric oxide, ferroferric oxide or nickel-based alloy. The modified nanoparticles are modified nano silicon dioxide or modified nano aluminum oxide.
7. The method according to claim 5, characterized in that The particle size of the shell of the core-shell magnetic nano-microsphere is 50-500nm, and the particle size of the core is 50-100nm; the particle size of the modified nano-particle is 10-50nm.
8. The method according to claim 5, characterized in that The pre-softened inorganic fiber is placed in a prepared surface treatment liquid for treatment, comprising: (21) adding the penetrant, cosolvent, other functional additives and pH adjuster into water and stirring to obtain a mixed mother solution; (22) placing the pre-softened inorganic fiber in the mixed mother solution for reaction under mechanical conditions to obtain a reaction mixture; (23) Adding magnetic nanospheres with a core-shell structure and modified nanoparticles to the reaction mixture in batches, and removing organic matter on the surface of the inorganic fiber by using a magnetic field after the reaction to modify the surface of the inorganic fiber.
9. The method according to claim 8, further comprising, after step (23), the steps of washing and drying the surface-modified inorganic fibers in sequence.
10. An inorganic fiber, characterized in that: The modified product is obtained by the modification method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation process method of high-temperature-resistant composite material
CN109608672A
Production method of electronic-grade glass fiber cloth
CN110258120A